Anti-inflammatory Effects of Spores Derived from Probiotic Strains Bacillus subtilis natto and Bacillus coagulans Hammer on Human Intestinal Epithelial Cells In Vitro - Khodamoradi, Elham; Yadegar, Abbas; Minai-Tehrani, Dariush (Novelty in Biomedicine, 2024)
Background: Probiotic administration can be an effective treatment against intestinal inflammation. This study aimed to assess the potential effects of spores isolated from probiotic strains Bacillus subtilis natto and Bacillus coagulans Hammer on inflammation induced by lipopolysaccharide (LPS) in human colon epithelial cells in vitro. Materials and Methods: The viability of HT-29 cells treated with spores derived from B. subtilis natto and B. coagulans Hammer (MOI 10, 100, 1000), as well as LPS (10 µg/ml) was assessed. The anti-inflammatory effects of spores were examined on HT-29 cells that were pre-stimulated with LPS. The expression level of IL-6 and TLR4 genes in HT-29 cells was quantified after 24 h using RT-qPCR. Results: There was no significant reduction in the viability of HT-29 cells after exposure to LPS and various MOIs of probiotic spores. Stimulation of HT-29 cells with LPS significantly increased the expression level of IL-6 and TLR4 in comparison to control (P < 0.0001). Spores isolated from both probiotic strains, B. subtilis natto and B. coagulans Hammer, caused a significant reduction in the gene expression of IL-6 and TLR4 in HT-29 cells compared to LPS control (P < 0.0001). Conclusion: The findings of this study suggest that probiotics-derived spores may exert anti-inflammatory effects through interference with the LPS signaling pathway in colon cancer HT-29 cell line.